Conservation of crisp lettuce in different post-harvest storage conditions - Schvambach, Mariana Izabel; Vargas Andriolli, Bruna; Fernandes de Souza, Priscila; Barcelos Oliveira, Jorge Luiz; Pescador, Rosete (Revista Ceres, 2025)
The objective of this work was to evaluate the post-harvest quality and the final storage time of the hydroponic crisp lettuce ‘Brida’, conditioned in different types of plastic packaging and environments. The statistical design was a completely randomized 3x2 factorial design, with 3 types of packages (control (without plastic packaging), perforated plastic packaging and closed plastic packaging) and 2 types of environments refrigerated (± 5 °C) and non-refrigerated (± 23 °C). Fresh leaf weight loss, relative SPAD content, total soluble solids content (TSS), pH, total titratable acidity (TTA), chlorophyll a and b, carotenoids and final storage time were measured. There was a decrease in the parameters of fresh mass, acidity, total soluble solids, and relative content of SPAD chlorophyll in refrigerated lettuce compared to uncooled. The use of packages also influenced post-harvest quality and closed packs resulted in lower values. It is concluded that the post-harvest quality of lettuce is better when they are refrigerated and packed in sealed packages.